Hubungan Peran Orang Tua Dan Pengetahuan Kesehatan Reproduksi Remaja Dengan Perilaku Seksual Pra Nikah Siswa Di Sma Kabupaten Cilacap - Evi Hidayati Hasanah; Ragil Setiyabudi (Jurnal Keperawatan Muhammadiyah, 2020)
Quantitative descriptive research using cross sectional design. The population was 96 and the sample was 74 students, taken by cluster sampling techniques. Data collection using a questionnaire. Data analysis using chi square statistical tests.The results showed that the majority of respondents were 16 years old (45.9%). Most of the respondents were male (54.1%). Most of them were interested in the opposite sex (51.4%). There were 56.8% of respondents who had a good parents role. There were 59.5% of respondents who had good knowledge of reproductive health. There were 20.3% of respondents who got bad pre-marital sexual behavior. There is a relationship between the role of parents (p-value = 0,0001) and reproductive health knowledge (p-value = 0,0001) with pre-marital sexual behavior of students in senior high schools.